(untitled) (Sambahak: Human Rights Journal, 2024)
The gender wage gap, a persistent issue across global labor markets, represents a significant challenge to achieving equality in remuneration for equal work. Despite international frameworks advocating for gender equality and equal pay, such as the UDHR, ICCPR, ICESCR, and CEDAW, alongside ILO Conventions No. 100 and No. 111, ILO, substantial disparities remain. Against this backdrop, this paper explores the intersection of labor rights, wage discrimination, and gender equality within the context of Nepal. The analysis highlights the entrenched global issue of wage discrimination, emphasizing that, despite legal advancements and constitutional guarantees in Nepal, the gender wage gap remains prevalent. Afterward, the article delves into the provision of the Labor Act of 2074 that aligns with these international principles and judicial precedents that underscore the principle of equal pay. Finally, the paper concludes with recommendations to address these challenges, including stricter enforcement of existing laws, increased gender equality initiatives, awareness campaigns, support for female trade unions, and the establishment of a dedicated Equal Remuneration Act. These measures aim to bridge the wage gap and foster a more equitable labor market in Nepal, reflecting a broader commitment to gender equality and economic justice.